Prevention of Non-procedural Indonesian Migrant Workers in the Riau Islands, Indonesia - Kurniawan, Deni; Rahmi, Khairi (Journal of Governance and Public Policy, 2026)
The Riau Islands, as a border region with Malaysia, have become a major transit point for prospective non-procedural Indonesian migrant workers before they are sent to Malaysia. Most non-procedural Indonesian migrant workers come from outside the Riau Islands Province and use two routes: the official route through international ports and the illegal route through unofficial channels. Economic factors and weak oversight in border areas are the main reasons why the Riau Islands have become a transit area. This study aims to analyze inter-agency cooperation in preventing illegal Indonesian migrant workers in the Riau Islands. This study uses a qualitative approach, in which data are obtained from in-depth interviews with BP3MI Riau Islands, Bakamla West Zone, and KKPPMP Batam Riau Islands, as well as from other secondary sources. Using Hasibuan's (2006) coordination theory, this study focuses on four indicators: unity of action, communication, division of labor, and discipline. The results revealed three main challenges. First, unclear regulations, particularly in Law No. 18 of 2017, make the prevention of non-procedural Indonesian migrant workers ambiguous. Second, BP3MI Riau Islands has not established a technical team and maritime fleet to support surveillance. Third, insufficient resources such as personnel, facilities, and budget hinder the effectiveness of cooperation. In conclusion, better coordination between agencies and optimization of resources are needed to strengthen surveillance. Structured cooperation is expected to overcome obstacles and enhance the effectiveness of preventing non-procedural Indonesian migrant workers in the Riau Islands region.